General Versus Regional Anesthesia in Sacrospinous Ligament Fixation for Pelvic Organ Prolapse: Assessment of a National Database. Issue 2 (February 2023) - Romanova, Anna; Gaigbe-Togbe, Bertille; Lieberman, Daniel; Seaman, Catherine; Woodbury, Carson; Tran, Ann; Hardart, Anne; Dabney, Lisa
Abstract : Importance: Sacrospinous ligament fixation is a prolapse repair surgical procedure that can be performed under general or regional anesthesia. Little is known about the impact of anesthesia on postoperative outcomes. Objectives: The primary objective of this study was to compare 30-day complication rates for patients undergoing sacrospinous ligament fixation by anesthesia type. Secondary objectives were to assess factors associated with type of anesthesia selected. Study Design: This was a retrospective cohort analysis of the American College of Surgeons National Surgical Quality Improvement Program for the years of 2015 to 2020. Cases were selected based on procedural codes for sacrospinous ligament fixation and diagnostic codes for prolapse. Complications, readmissions, and reoperations were compared between general versus regional anesthesia cohorts. Results: A total of 2, 984 cases were included with 2, 742 (91.9%) performed under general and 242 (8.1%) performed under regional anesthesia. The regional anesthesia cohort was older (69.2 vs 65.4 years old; P < 0.001) with no differences in medical history variables. Fewer patients in the regional anesthesia cohort were Hispanic (0.4% in regional vs 10.8% in general cohorts, P < 0.001). More superficial surgical site infections (2.5% vs 0.8%, P = 0.026) and cardiac complications (0.8% vs 0.1%, P = 0.035) were noted in the regional anesthesia cohort. However, multivariable regression analysis showed that anesthesia type was not associated with increased rates of minor or major complications. Conclusions: Mode of anesthesia was not a significant predictor of minor or major complications. Racial and ethnic differences in mode of anesthesia warrant further investigation to reduce racial disparities.